Is there a need for a CT scan of the pancreatic phase? A perfusion and simulation study of the pancreas, an HCC, and the kidney cortex - Cressoni, Massimo; Cadringher, Paolo; Colarieti, Anna; Darvizeh, Fatemeh; Cozzi, Andrea; Cina, Claudio; Zanardo, Moreno; Ambrogi, Federico; Ippolito, Davide; Sardanelli, Francesco (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2025)
To explore the peak enhancement time of a hepatocellular carcinoma, the pancreas, and the kidney cortex and its determinants.We obtained a time enhancement curve from the perfusion CT scans of 11 advanced HCC patients (40 volumes at 1.25 s time interval, slab slice 90 mm, bolus of 50 ml of iodinated contrast agent, 350 g iodine/ml, flow 5 ml/s). Small regions of interest were drawn on the abdominal aorta, the HCC, the cortex of the right kidney, and on the pancreas. The behavior of the contrast agent in the capillary and in the surrounding tissue was further explored with a finite element model.The peak enhancement time of the pancreas did not differ from that of the HCC (10±3 vs. 11±4 s, p=0.9), while the peak enhancement time of the kidney tended to be a few seconds earlier (8±1 s, p=0.082 vs. pancreas and p=0.069 vs. kidney). Simulation showed that the time span in which the tissue enhancement remained within 10% of its peak value was similar across all capillary densities and ranged between 26−38 s for a capillary density of 80 per mm to 30–60 s for a capillary density of 10.The plateau tissue enhancement clinically acquired in the “late arterial phase” should be adequate both for the detection of hypervascular liver lesions such as HCCs and for obtaining peak pancreatic enhancement to detect hypovascular lesions.
Keywords: contrast agents; pancreatic adenocarcinoma; computed tomography; arterial phase; hepatocarcinoma; perfusion imaging